Bricklaying process in construction site / Hanis Wahidah Mohamad Dashuki - Mohamad Dashuki, Hanis Wahidah (Universiti Teknologi MARA, Perak, 2022)
Brickwork is masonry produced by a bricklayer, using bricks and mortar. Typically, rows of bricks called courses are laid on top of one another to build up a structure such as a brick wall. However, currently there is limited research conducted on proper bricklaying process in residential building. Therefore, this report will discuss the bricklaying process in a construction site. This report was conducted for the Construction of One Storey Bunglow House at Lot 446, Mukim Taking, Daerah Mentuan, Jajahan Bachok, Kelantan that owned by En Mohd Azman Bin Mohamed Firdaus. The objective of this report is to explain the bricklaying process and problem occurs during the processes. In addition, this report is conducted by using three appropriate method such as observation, interview, document review. As a result, to conduct a bricklying process, there are 10 step need to follow which is plan out the wall, prepare all the materials that are needed, make guide post or gauging rods, clamp a string on first guide line and lay the first row of bricks for a dry run, laying the next course of bricks, plastering the Wall. However, there are two problems occurred during the bricklaying process for example the weather and the material management. As the conclusion, the proper bricklaying process is crucial to understand by contractor who are willing to construct the wall in the future.